One man's music : the life and times of Texas songwriter Vince Bell - Bell, Vince (North Texas lives of musicians series, 2009)
Presents the story of Vince Bell, Texas singer/songwriter. This book chronicles Vince Bell's life and near death on the road. It reveals what it means to live for one's art.